2015
DOI: 10.1097/inf.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Oropharyngeal Carriage of Meningococcus in Portugal by Group and Clonal Complex 6 Years After Adolescent Vaccine Campaign

Abstract: Portugal introduced (2+1) conjugate Meningococcal group C vaccine in 2006 with high coverage catch up to 18 years and has given only 1 dose at 1 year since 2012. Among 601 student oropharyngeal swabs, meningococcal carriage rate was 13.3% (A-0%, B-5.3%, C-0.3%, W-0.2%, X-0.2% and Y-1.7%). C and W strains were of potentially disease-causing clonal complexes (cc) but not the hyperinvasive cc11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 14 publications
3
16
0
Order By: Relevance
“…Putting swabs into broth, storing them frozen and processing them later in batches has been the norm for many years in pneumococcal carriage studies and is now becoming established in meningococcal swabbing studies as well. 10,20,22 Genogrouping is more efficient than conventional serogrouping techniques using antisera in studies of carriage bacteria, which often express only low levels of capsular antigens. 9,10 The use of "lawn cultures" as a means to amplify DNA for molecular detection has been described in the literature on pneumococcal carriage studies.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 3 more Smart Citations
“…Putting swabs into broth, storing them frozen and processing them later in batches has been the norm for many years in pneumococcal carriage studies and is now becoming established in meningococcal swabbing studies as well. 10,20,22 Genogrouping is more efficient than conventional serogrouping techniques using antisera in studies of carriage bacteria, which often express only low levels of capsular antigens. 9,10 The use of "lawn cultures" as a means to amplify DNA for molecular detection has been described in the literature on pneumococcal carriage studies.…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…10,20,22 Genogrouping is more efficient than conventional serogrouping techniques using antisera in studies of carriage bacteria, which often express only low levels of capsular antigens. 9,10 The use of "lawn cultures" as a means to amplify DNA for molecular detection has been described in the literature on pneumococcal carriage studies. 24 In our hands it seems to compensate almost entirely for the deficits in sensitivity of genogrouping qPCRs when compared to standard culture and testing of isolates.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies have focused on the optimization of methods for collecting pharyngeal swabs; these studies have shown that a peroral swab taken behind the uvula is most likely to yield a positive result and that taking two sequential swabs increases sensitivity (46). Until recently, little has been done to improve methods of transport (7, 8), and we are aware of only two studies aimed at improving the identification of meningococci by using molecular methods (9, 10). PCR testing on DNA extracted directly from a swab has been employed in some studies, but a recent investigation of UK adolescents showed that this method was less sensitive than conventional culture followed by PCR (11).…”
Section: Introductionmentioning
confidence: 99%